A top-down analysis: Determining photovoltaics R&D; investments from patent analysis and R&D; headcount - Breyer, C; Meiss, J; Birkner, C; Goldschmidt, J; Riede, M (Elsevier, 2013)
For alternative energy technologies like photovoltaics (PV), the analysis of Research and Development (R&D;) expenses is important to observe and understand market dynamics. This is, in turn, essential for policymakers. However, the quantitative evaluation of global corporate R&D; investments is a challenging task due to unavailability or high scatter of precise data. Here we present a top-down approach to estimate the current and global historic cumulated PV R&D; investments based on international PV patent applications. High growth rates of PV-related patents and R&D; headcount accompany growth and development of the PV market and are an excellent indicator to analyze R&D; investments. With this approach, current annual corporate PV R&D; investments are found to be about 6000. m? and show a rapidly increasing trend on a global scale.